Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Konsumen Alfamart Griya Parungpanjang - Riska Ristiana; Sinta Sulistiani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the effect of promotion and price on consumer purchasing decisions at Alfamart Griya Parungpanjang, both partially and simultaneously. This research method uses a quantitative method with a sample of 100 respondents, data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, determination coefficient analysis test, t test and f test. Based on the results of the partial test, promotion (X1) has a positive and significant effect on the purchasing decision variable (Y). It is proven by the calculated t of 12.201>1.984 and a significance value of 0.000<0.05. Based on the results of the partial test, price (X2) has a positive and significant effect on the purchasing decision variable (Y), it is proven by the calculated t value of 10.117>1.984 and a significance value of 0.000<0.05. Based on the results of the simultaneous test, promotion (X1) and price (X2) simultaneously have a positive and significant influence on purchasing decisions (Y), as evidenced by the F-count value of 80.281>3.09 and a significance value of 0.000<0.05